Sweat analysis for urea sensing: Trends and challenges - Narayanamurthy, Vigneswaran; Abhishek Shankar, Futane; Senthil, Mallika; Srinivasan, Arthi; Ramakrishnan, Kalpana (Royal Society of Chemistry, 2023)
With increasing population there is a rise in pathological diseases that the healthcare facilities are grappling with. Sweat-based wearable technologies for continuous monitoring have overcome the demerits associated with sweat sampling and sensing. Hence, sweat as an alternative biofluid holds great promise for the quantification of a host of biomarkers and understanding the functioning of the body, thereby deducing ailments quickly and economically. This comprehensive review accounts for recent advances in sweat-based LOCs (Lab-On-Chips), which are a likely alternative to the existing blood-urea sample testing that is invasive and time-consuming. The present review is focused on the advancements in sweat-based Lab-On-Chips (LOCs) as an alternative to invasive and time-consuming blood-urea sample testing. In addition, different sweat collection methods (direct skin, near skin and microfluidic) and their mechanism for urea sensing are explained in detail. The mechanism of urea in biofluids in protein metabolism, balancing nitrogen levels and a crucial factor of kidney function is described. In the end, research and technological advancements are explained to address current challenges and enable its widespread implementation.